2008
DOI: 10.1158/0008-5472.can-07-0782
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Expression during Immortalization and Breast Cancer Progression

Abstract: Identification of molecular aberrations in premalignant human mammary epithelial cells (hMEC), the precursors for breast cancers, is a central goal in breast cancer biology. Recent studies implicated expression of cyclooxygenase 2 (COX-2) as a marker to identify precursor cells for breast cancer. In this study, we analyzed COX-2 expression in preselection and postselection hMEC cells and observed similar COX-2 levels in both cells. Interestingly, immortalization of postselection cells using various methods lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Similarly, COX-2 overexpression has been linked to disease-free and overall survival in some studies (4,7,8,11), whereas others did not show a significant correlation with clinicopathologic variables (5, 9). Moreover, the expression of COX-2 has been detected at a higher frequency in tumor tissue compared with normal human breast tissue by Soslow et al (6), but others have found the opposite (7,52). And although overexpression of COX-2 has been shown to favor tumor growth by stimulating cell proliferation (12), angiogenesis (13), invasiveness (14), and inhibition of apoptosis (15), recent data from Zhao and colleagues (52) showed that COX-2 downregulation by small interfering RNA in breast cell lines did not have any effect on cell proliferation, migration, or invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, COX-2 overexpression has been linked to disease-free and overall survival in some studies (4,7,8,11), whereas others did not show a significant correlation with clinicopathologic variables (5, 9). Moreover, the expression of COX-2 has been detected at a higher frequency in tumor tissue compared with normal human breast tissue by Soslow et al (6), but others have found the opposite (7,52). And although overexpression of COX-2 has been shown to favor tumor growth by stimulating cell proliferation (12), angiogenesis (13), invasiveness (14), and inhibition of apoptosis (15), recent data from Zhao and colleagues (52) showed that COX-2 downregulation by small interfering RNA in breast cell lines did not have any effect on cell proliferation, migration, or invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of COX-2 has been detected at a higher frequency in tumor tissue compared with normal human breast tissue by Soslow et al (6), but others have found the opposite (7,52). And although overexpression of COX-2 has been shown to favor tumor growth by stimulating cell proliferation (12), angiogenesis (13), invasiveness (14), and inhibition of apoptosis (15), recent data from Zhao and colleagues (52) showed that COX-2 downregulation by small interfering RNA in breast cell lines did not have any effect on cell proliferation, migration, or invasion. In addition, the same group provided evidence that COX-2 overexpression did not provide an oncogenic advantage to transformed breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…COX-1 is responsible for generating PGs for normal physiological function, whereas COX-2 is an early gene, which is rapidly induced by a variety of agents, including lipopolysaccharides, cytokines, growth factors and tumor promoters. Many studies have consistently showed that mRNA and protein levels of COX-2, but not COX-1, are markedly elevated during various neoplastic progressions (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, neither peptides nor celecoxib induced cytotoxicity in MCF-7 cells. Unlike KB cells, MCF-7 cells do not express COX-2 (Zhao et al 2008). Although all peptides significantly reduced tumor cell proliferation, peptides P1, P4, and P6 showed maximum inhibition.…”
Section: Discussionmentioning
confidence: 93%
“…COX-2 is undetectable in most tissues, but its expression can be rapidly induced by a variety of stimuli like growth factors, inflammatory cytokines, tumor promoters, ionizing radiation, and carcinogens. Immuno-histochemical, reverse transcription (RT)-PCR and in situ hybridization studies have shown very low or no expression of COX-2 in normal human and hamster oral tissues, while it was up-regulated in oral precancerous lesions and overexpressed in dysplasia and OSCC (Li et al 2005;Shibata et al 2005;Sawhney et al 2007;Pandey et al 2008) besides other malignancies (Howe et al 2001;Marnett and DuBois 2002;Rigas and Kashfi 2005;Wu 2005;Zhao et al 2008). The increased COX-2 expression was reported to be associated with malignant transformation and advancing clinical stage and prognosis (Grau et al 2004;Saba et al 2009) in patients with head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%